2010
DOI: 10.1111/j.1751-3928.2010.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

REE, Mn, Fe, Mg and C, O Isotopic Geochemistry of Calcites from Furong Tin Deposit, South China: Evidence for the Genesis of the Hydrothermal Ore‐forming Fluids

Abstract: The Furong tin deposit in the central Nanling region, South China, consists of three main types of mineralization ores, i.e. skarn-, altered granite-and greisen-type ores, hosted in Carboniferous and Permian strata and Mesozoic granitic intrusions. Calcite is the dominant gangue mineral intergrown with ore bodies in the orefield. We have carried out REE, Mn, Fe, and Mg geochemical and C, and O isotopic studies on calcites to constrain the source and evolution of the ore-forming fluids. The calcites from the Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Therefore, regardless of the exact mechanism, it is reasonable that the Fe-Mn nanoparticle impurities may play an important role on the enrichment of MREE and HREE in calcites. This inference is also evidenced by Shuang et al (2010), which reported three types of calcites present in the Furong tin deposit, and a negative relationship also occurs between Fe+Mn (wt%) and LREE/HREE ratios (Fig. 9).…”
Section: Ree and Fe Mnmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, regardless of the exact mechanism, it is reasonable that the Fe-Mn nanoparticle impurities may play an important role on the enrichment of MREE and HREE in calcites. This inference is also evidenced by Shuang et al (2010), which reported three types of calcites present in the Furong tin deposit, and a negative relationship also occurs between Fe+Mn (wt%) and LREE/HREE ratios (Fig. 9).…”
Section: Ree and Fe Mnmentioning
confidence: 55%
“…9. The LREE/HREE versus Fe+Mn diagram for calcites from the Furong tin deposit (data from Shuang et al, 2010).…”
Section: Ree and Fe Mnmentioning
confidence: 99%